2007
DOI: 10.1017/s0043933907001444
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin requirements: is there basis for re-evaluating dietary specifications?

Abstract: There has been little work conducted over the last 40 years on estimating vitamin requirements of poultry, and so consequently NRC (1994) values are still often quoted as standards. A review of this information indicates many values are estimates, or extrapolated from comparable species, or as with broiler breeders, simply not given. The current concern related to formulating vitamin levels in poultry diets is the assumption that change in genetic potential of layers and meat birds necessitates re-evaluation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 33 publications
2
27
0
8
Order By: Relevance
“…In this study, increased growth performance was observed in ducklings fed a diet with high-vitamin premix designed according to the recommendations in the DSM Vitamin Supplementation Guidelines. These observations clearly demonstrate a shortcoming in the current NRC (1994) vitamin recommendations for ducks and are highly consistent with the view of Leeson (2007) that the vitamin requirements of poultry require re-evaluation. Interestingly, maternal and progeny dietary vitamin regimens interactively affected growth performance in the first 14 days post hatching.…”
Section: Discussionsupporting
confidence: 82%
“…In this study, increased growth performance was observed in ducklings fed a diet with high-vitamin premix designed according to the recommendations in the DSM Vitamin Supplementation Guidelines. These observations clearly demonstrate a shortcoming in the current NRC (1994) vitamin recommendations for ducks and are highly consistent with the view of Leeson (2007) that the vitamin requirements of poultry require re-evaluation. Interestingly, maternal and progeny dietary vitamin regimens interactively affected growth performance in the first 14 days post hatching.…”
Section: Discussionsupporting
confidence: 82%
“…Vários estudos realizados para determinar as necessidades de vitaminas para frangos foram realizados em condições controladas e/ou com dietas purificadas ou semipurificadas, de alta digestibilidade, sendo compostas por ingredientes pouco usuais na alimentação de frangos, o que também demonstra a baixa correlação com a realidade no campo (LEESON, 2007). Além disso, poucos são os trabalhos conduzidos nos últimos 30 anos para estimar as exigências de vitaminas para frangos, os quais apresentam maior potencial genético de crescimento, com melhora superior a 20% na conversão alimentar (CA) (PÉREZ-VENDRELL et al, 2002) e ganho de peso médio diário 87% superior (de 26,8g dia -1 em 1970 a 50g dia -1 em 2000) (BARROETA et al, 2002).…”
Section: Recomendaçõesunclassified
“…Geralmente respostas significativas do sistema imune ocorrem apenas quando as vitaminas são suplementadas em níveis pelo menos 10 vezes superiores aos do NRC (1994) ou duas a três a vezes maiores que os utilizados comercialmente (LEESON, 2007).…”
Section: Recomendaçõesunclassified
See 1 more Smart Citation
“…Cortinas et al (2005) concluíram que a suplementação com até 200mg/kg de α-tocoferol previne até 88% da máxima oxidação lipídica, no entanto níveis superiores a este não apresentaram melhora na estabilidade da carne de coxas de frangos. Segundo Leeson (2007), geralmente a suplementação de 100-400UI de vitamina E/kg de dieta tem demonstrado promover a qualidade da carne na maioria dos estudos.…”
unclassified